Age at menarche, environmental stress, and social inequality: Evidence from Poland in the 1930s-1950s - Liczbińska, Grażyna; Brabec, Marek; Piontek, Janusz; Malina, Robert M (American journal of human biology, 2023)
OBJECTIVE: To address the relationship between socioeconomic factors and age of menarche among Polish women born and reared in periods that varied considerably in environmental stresses: the Great Depression of the 1930s, the interval of World War II, and the interval of communist rule following World War II through the 1950s. METHODS: The data set included information on age at menarche and socioeconomic status (SES) of 718 women born during the Great Depression (n = 182), WWII (n = 189), and post-WWII through the 1950s (n = 347). A structured semi-parametric statistical model (generalized additive model [GAM] class) was used for analysis. An ANOVA-like linear model was used to test for marginal effects of SES-related factors and their interactions together with nonparametric seasonal effect. RESULTS: The influence of period of birth, month of birth, region of early childhood, and father's education, and the interaction between period of birth and father's education on age at menarche were statistically significant. During the economic crisis and the interval of WWII, differences in ages at menarche between the extreme categories of father's education were marked. The differences in ages at menarche between women from the lowest and highest social groups were markedly reduced among women born during the post-war interval. In addition, women born in February-March attained menarche earlier than women born in September-October. CONCLUSIONS: Unpredictable conditions associated with the economic crisis and war conditions had a stronger impact on age at menarche among women from families of lower SES compared to women from better economic circumstances. Individuals born and reared in low SES conditions likely suffered more severe deterioration across the spectrum of the standard of living and quality of life compared to those with a higher SES.
Keywords: Socioeconomic Factors; společenská třída; věkové faktory; Poland; menarche; předškolní dítě; kvalita života; Menarche; socioekonomické faktory; Child, Preschool; lidé; Female; Quality of Life; Polsko; ženské pohlaví; Age Factors; Social Class; Humans